Optical properties of vanadium oxide nanostructures synthesized by laser pyrolysis - Shikwambana, Lerato David (My University, 2012)
In this work, the primary investigation has been on the development of the laser pyrolysis setup and its optimization for the synthesis of nano-size VO2-x films. More specifically the focus was on making VO2-x depositions using various laser pyrolysis parameters and establish in this way (1) an optimum laser wavelength threshold for the photon induced dissociation of the molecular precursors while the thermal contribution was kept minimal by using low power density (laser energy of 30 W) and (2) the lower threshold for pure thermal contributions by working with wavelengths far from resonance in order to minimize pure photon induced contributions. The interest in synthesizing nano-size VO2-x materials stems from the low metal-insulator transition temperature at near room temperature with opto-electronic and thermo-electronic properties that can be used in specialised applications. A large number of samples were synthesized under various conditions and annealed under argon atmosphere for 17 hours. XRD analysis identified the VO2 (B) and/or β-V2O5 vanadium oxide phases characteristic for certain samples grown under optimum conditions. Raman spectroscopy also confirmed these vanadium oxide phases with bands observed at 175, 228, 261, 303, 422 and 532 cm-1. SEM analysis revealed a plethora of different nanostructures of various size and shapes. The particles have a range of sizes between 55 nm to 185 nm in diameter. The particles showed morphologies which included nano-rods, nanospheres and nano-slabs. An interesting phenomenon was observed on the samples synthesized with high power density, which was observed and reported by Donev iii et al. EDS analysis on the particles was also used to probe the elemental composition of the sample. Optical studies were performed on the samples which showed transitions in the visible and infrared region in accordance with the ones observed in the international literature using different nano-synthesis methods.
M.Sc., Faculty of Science, University of the Witwatersrand, 2011
Keywords: Vanadium; Nanostructures; Nanostructured materials; Nanotechnology